(untitled) (Biological Sciences - PJSIR, 2021)
The adverse environmental and human health impact of chemical use against micro-organism is profoundly increased. For this motive, substitute methods to minimize chemicals are being developed. One of the effective methods is use plant extracts which having natural antimicrobial properties. The aim of this study was to evaluate ethanolic extract of Datura stramonium L. (leaves) and Hippophae rhamnoides (fruits) against the selected micro-organisms. Results revealed that mean zone of inhibition for bacterial species ranged from 23±0.72 to 27±1.24 mm in case of Hippophae rhamnoides and from 21±0.79 to 30±1.06 mm in case of D. stramonium leaves respectively. For antifungal activity, the inhibition zone ranges from 39.42±1.07 to 47.22±2.11 mm in case of D. stramonium and from 38.42±1.19 to 48.46±2.32 mm in case of H. rhamnoides. However, sensitivity reaction of bacterial and fungal species against each plant extract was also differential. D. stramonium showed highest toxic effect against E. coli (30±1.06 mm)) and Aspergillus flavus (47.22±2.11mm). Whereas, H. rahmnoides showed highest zone of inhibition against bacterial species (B. subtilis 27±1.24 mm) and fungal species (R. stolonifer 48.46±2.32 mm). Both plant extract exhibited antimicrobial properties, which could be used against micro-organisms.